Effect of Tucatinib on Cardiac Repolarization in Healthy Volunteers - Ariel R. Topletz-Erickson; JoAl G. Mayor; Hsu-Tai Liu; Layth I. Abdulrasool; Christopher J. Endres (Adis, Springer Healthcare, 2023)
Abstract Background and Objective Tucatinib is a selective tyrosine kinase inhibitor of the human epidermal growth factor receptor 2 (HER2) approved to treat metastatic HER2-positive breast and colorectal cancers. The International Council for Harmonisation of Technical Requirements for Human Use (ICH) E14 guideline mandates that new drugs are assessed for potential effects on cardiac repolarization through electrocardiogram (ECG) evaluation in a QT/corrected QT (TQT) study. Methods We evaluated the effect of tucatinib on cardiac repolarization in healthy volunteers in a phase I, randomized, partially double-blind, placebo-and positive-controlled three-period crossover study. The primary endpoint was the placebo-corrected change from baseline in QT interval values, corrected for heart rate using Fridericia's method (ΔΔQTcF). Results After achieving steady-state tucatinib exposures with 300 mg twice daily, the observed ΔΔQTcF ranged from −2.9 msec at 2 hours post-dose to 0 msec at 4 hours post-dose. The upper bound of the 90% confidence interval (CI) was below 5 ms at all post-dose timepoints. Assay sensitivity was confirmed as the lower bound of the 90% CI and was >5 ms following moxifloxacin dosing. As the mean ΔΔQTcF of tucatinib was predicted to be −  1.80 ms (90% CI −  3.90, 0.30) at clinically relevant tucatinib concentrations (511 ng/mL), an effect of tucatinib on QTcF exceeding 10 ms was excluded within observed ranges of tucatinib (up to ~1000 ng/mL). Tucatinib had no clinically relevant effect on heart rate or cardiac conduction. The safety profile of tucatinib was manageable after multiple doses. Conclusion Tucatinib had no clinically relevant effects on studied ECG parameters. This study constitutes a clearly negative TQT study per ICH E14 guidance. Clinical Trial Registration This trial (NCT03777761) was registered on 17 December 2018.